Proteomics and metabolic phenotyping define principal roles for the aryl hydrocarbon receptor in mouse liver - Jian Jin; Banrida Wahlang; Monika Thapa; Kimberly Z. Head; Josiah E. Hardesty; Sudhir Srivastava; Michael L. Merchant; Shesh N. Rai; Russell A. Prough; Matthew C. Cave (Elsevier, 2021)
Dioxin-like molecules have been associated with endocrine disruption and liver disease. To better understand aryl hydrocarbon receptor (AHR) biology, metabolic phenotyping and liver proteomics were performed in mice following ligand-activation or whole-body genetic ablation of this receptor. Male wild type (WT) and Ahr-/- mice (Taconic) were fed a control diet and exposed to 3,3',4,4',5-pentachlorobiphenyl (PCB126) (61 nmol/kg by gavage) or vehicle for two weeks. PCB126 increased expression of canonical AHR targets (Cyp1a1 and Cyp1a2) in WT but not Ahr-/-. Knockouts had increased adiposity with decreased glucose tolerance; smaller livers with increased steatosis and perilipin-2; and paradoxically decreased blood lipids. PCB126 was associated with increased hepatic triglycerides in Ahr-/-. The liver proteome was impacted more so by Ahr-/- genotype than ligand-activation, but top gene ontology (GO) processes were similar. The PCB126-associated liver proteome was Ahr-dependent. Ahr principally regulated liver metabolism (e.g., lipids, xenobiotics, organic acids) and bioenergetics, but it also impacted liver endocrine response (e.g., the insulin receptor) and function, including the production of steroids, hepatokines, and pheromone binding proteins. These effects could have been indirectly mediated by interacting transcription factors or microRNAs. The biologic roles of the AHR and its ligands warrant more research in liver metabolic health and disease.